SISWA SEHAT, MASA DEPAN HEBAT: EDUKASI PERILAKU HIDUP BERSIH DAN SEHAT DI SD NEGERI 25 MEULABOH KEC. JOHAN PAHLAWAN KAB ACEH BARAT - Rika Andriani; Ratnawati Bancin; Erlia Rosita; Zakiyah Zakiyah; Samsidar Samsidar (JURNAL PENGABDIAN KEPADA MASYARAKAT BIDANG KESEHATAN, 2025)
The implementation of Clean and Healthy Living Behavior (PHBS) in schools is an absolute necessity along with the emergence of various diseases that often attack school-aged children (6-12 years). PHBS in schools is a set of behaviors practiced by students, teachers and the community in the elementary school environment as a result of learning, so that they are independently able to prevent disease, improve health and play an active role in creating a healthy environment. The purpose of this counseling activity is to provide students with understanding and awareness of clean and healthy living in everyday life both at home and at school. The target of this counseling is students of SD Negeri 25 Meulaboh. Based on the results of the evaluation after the activity, students understand more and are willing to apply clean and healthy living in everyday life.